2012
DOI: 10.1002/ejic.201200876
|View full text |Cite
|
Sign up to set email alerts
|

3‐(2‐Pyridyl)‐5‐(2‐thienyl)pyrazole and Complexes of Its Anion with Lithium, Magnesium, Calcium, and Zinc Ions

Abstract: Keywords: Zinc / Lithium / Calcium / Magnesium / N ligands 5-(2-Furanyl)-3-(2-pyridyl)pyrazole (1) and 3-(2-pyridyl)-5-(2-thienyl)pyrazole (2) oligomerize through hydrogen bridges in the solid state to yield tetramers and dimers, respectively. The pyrazole units are very acidic and, therefore, deprotonation of 2 with the organometallic reagents LiN(SiMe 3 ) 2 , PhLi, ZnMe 2 , and ZnEt 2 allows the synthesis of (tetrahydrofuran)lithium 3-(2-pyridyl)-5-(2-thienyl)pyrazolate (3a), bis[methylzinc 3-(2-pyridyl)-5-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Small aggregates, being soluble in common organic solvents, can be achieved if large substituents were kept at the central metal atoms as, for example, in dimeric bis[bis(trimethylsilyl)methylzinc 3, 5‐bis(2‐pyridyl)pyrazolate] 8. In order to ensure solubility in organic solvents, we investigated 5‐(2‐pyridyl)pyrazolates with phenyl9 and thienyl groups10 in 3‐position, which represent weak and soft Lewis‐bases. Herein we extend our investigations on 3‐(2‐furanyl)‐ ( 1 ),10 3‐(1‐adamantyl)‐ ( 2 ), and 3‐ferrocenyl‐5‐(2‐pyridyl)pyrazole ( 3 )11 with 3‐positioned substituents with significantly different steric and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Small aggregates, being soluble in common organic solvents, can be achieved if large substituents were kept at the central metal atoms as, for example, in dimeric bis[bis(trimethylsilyl)methylzinc 3, 5‐bis(2‐pyridyl)pyrazolate] 8. In order to ensure solubility in organic solvents, we investigated 5‐(2‐pyridyl)pyrazolates with phenyl9 and thienyl groups10 in 3‐position, which represent weak and soft Lewis‐bases. Herein we extend our investigations on 3‐(2‐furanyl)‐ ( 1 ),10 3‐(1‐adamantyl)‐ ( 2 ), and 3‐ferrocenyl‐5‐(2‐pyridyl)pyrazole ( 3 )11 with 3‐positioned substituents with significantly different steric and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure solubility in organic solvents, we investigated 5‐(2‐pyridyl)pyrazolates with phenyl9 and thienyl groups10 in 3‐position, which represent weak and soft Lewis‐bases. Herein we extend our investigations on 3‐(2‐furanyl)‐ ( 1 ),10 3‐(1‐adamantyl)‐ ( 2 ), and 3‐ferrocenyl‐5‐(2‐pyridyl)pyrazole ( 3 )11 with 3‐positioned substituents with significantly different steric and electronic properties. Quantum chemical calculations on monomeric 3‐phenyl‐5‐(2‐pyridyl)pyrazole showed that a hydrogen bridge between the pyridyl and the pyrazole units stabilizes a cis conformation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations